KAWASAN AGROPOLITAN KABUPATEN DONGGALA DALAM KONTEKS PENGEMBANGAN WILAYAH DAN SEBAGAI PUSAT PERTUMBUHAN WILAYAH BARU - Basri, Iwan Setiawan; Arifin, Rosmiaty (MEKTEK, 2010)
The development of agropolitan region is a sustainable development based on regional resources. Thedevelopment of agropolitan region is conducted by developing rural areas in terms of promoting the systemand works of a competitive, society based, sustainable, and decentralized agribusiness by utilizing theavailable resources. This work was conducted by developing an agropolitan regional planning in 2003.Three districts; Dolo, Sigi Biromaru, and Palolo has been chosen as the centre of development which wasdesignated as a new area. The three regions were hoped to stimulate and produce double effect fortriggering the development of the hinterland areas by utilizing their potency. The study was conducted in2005 before the three districts incorporated in Sigi regency in 2008. Therefore in this report, the threedistrict were designated as Donggala regency